Target costing in a stage-gate design system / Jan Alpenberg…[et al.] - Alpenberg, Jan; Alku, Jeton; Rashiti, Judita; Scarbrough, Paul (Faculty of Accountancy, 2016)
The importance of new product development is observed in recent research on dynamic capabilities and target costing (TC). With established concepts from literature on dynamic capabilities and TC, we examine possible path dependent conflicts in introducing TC to an organization using a traditional western product design approach. This study describes the attempt to add TC to a traditional stage-gate (SG) product development process. Implementing TC as a separate tool in an SG model raises the possibility that the sequential and rigorously "gated" design process would be in conflict with the iterative and multifunctional nature of TC. We find that conflict exists between the SG method and TC. This finding is consistent with criticisms on SG raised in literature. These criticisms include limitations on learning because of the truncation of sub-projects without iterations in TC. Moreover, we support the finding of a previous study that extremely rigorous gate evaluations reduce flexibility in the development system. We connect this previous study's observations with the concept of dynamic capabilities to make our analysis highly granular and to highlight the aspects of TC that are in conflict with SG-type design processes.